Active implants and scaffolds for tissue regeneration - Zilberman, Meital (Studies in mechanobiology, tissue engineering and biomaterials, 2011)
Active implants are drug or protein-eluting implants that induce healing effects, in addition to their regular task, for example support. This effect is achieved by controlled release of bioactive agents to the surrounding tissue. This book presents a broad overview of biomaterial platforms used in internal and external drug-eluting implants. The book is divided into four parts: 1. Drug-eluting implants; 2. Scaffolds for bone regeneration; 3. Scaffolds based on natural polymers; 4. New polymeric systems for active implants. The 18 reviews describe active implants in terms of matrix formats, incorporated drugs and their release profiles from the implants, as well as cell-implant interactions and functions. The effect of the process parameters on the micro or nano-structure and on the resulting drug release profiles, mechanical and physical properties, and other relevant properties, are emphasized. It is the first book to describe a broad range of active implants and present the frontier of knowledge in this field. The new biomaterial approaches for active implants described in this book enhance the tools available for clinically important biomedical applications.